2017
DOI: 10.1101/226837
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conformational control of translation termination on the 70S ribosome

Abstract: Translation termination ensures proper lengths of cellular proteins. During termination, release factor (RF) recognizes a stop codon and catalyzes peptide release.Conformational changes in RF are thought to underlie accurate translation termination.If true, the release factor should bind the A-site codon in inactive (compact) conformation(s), but structural studies of ribosome termination complexes have only captured RFs in an extended, active conformation. Here, we identify a hyper-accurate RF1 variant, and p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 49 publications
(99 reference statements)
1
11
0
Order By: Relevance
“…2 D ; 14 nM RF1), at a concentration approximately sevenfold below the lowest K D of RF1 for a modified stop codon—i.e., UAP. Under both conditions, RF1 rate constants were nearly identical for 70S complexes formed with UAA [420 nM RF1: k cat = (6.0 ± 0.1) × 10 −2 s −1 ; 14 nM RF1: k cat = (1.9 ± 0.1) × 10 −2 s −1 ] and UAG [420 nM RF1: k cat = (6.1 ± 0.1) × 10 −2 s −1 ; 14 nM RF1: k cat = 2.0 × 10 −2 s −1 ], which is in line with earlier reports ( 22 , 44 46 ). The rates of release on UAP [420 nM RF1: k cat = (4.7 ± 0.1) × 10 −2 s −1 ; 14 nM RF1: k cat = 1.6 × 10 −2 s −1 ] and UPG codons [420 nM RF1: k cat = (5.2 ± 0.1) × 10 −2 s −1 ; 14 nM RF1: k cat = (2.0 ± 0.1) × 10 −2 s −1 ] were similar to UAA and UAG, respectively.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…2 D ; 14 nM RF1), at a concentration approximately sevenfold below the lowest K D of RF1 for a modified stop codon—i.e., UAP. Under both conditions, RF1 rate constants were nearly identical for 70S complexes formed with UAA [420 nM RF1: k cat = (6.0 ± 0.1) × 10 −2 s −1 ; 14 nM RF1: k cat = (1.9 ± 0.1) × 10 −2 s −1 ] and UAG [420 nM RF1: k cat = (6.1 ± 0.1) × 10 −2 s −1 ; 14 nM RF1: k cat = 2.0 × 10 −2 s −1 ], which is in line with earlier reports ( 22 , 44 46 ). The rates of release on UAP [420 nM RF1: k cat = (4.7 ± 0.1) × 10 −2 s −1 ; 14 nM RF1: k cat = 1.6 × 10 −2 s −1 ] and UPG codons [420 nM RF1: k cat = (5.2 ± 0.1) × 10 −2 s −1 ; 14 nM RF1: k cat = (2.0 ± 0.1) × 10 −2 s −1 ] were similar to UAA and UAG, respectively.…”
Section: Resultssupporting
confidence: 92%
“…However, mutational studies also identified other amino acids that were involved in stop codon recognition, implicating that the tripeptide anticodon alone is not sufficient for providing translation termination ( 20 ). Remarkably, mutations altering the codon specificity of RFs were only identified outside of the potential codon recognition site ( 20 22 ).…”
mentioning
confidence: 99%
“…The effects of GR n or PR n on peptide bond formation in E. coli ribosome were tested in an in vitro assay that reacts the 70S ribosome loaded with [ 35 S]-fMet-tRNA fMet in the P site with puromycin, an A-site tRNA mimic, and measures the release of the resulting dipeptide containing formylmethionine covalently bonded to puromycin, as described (Svidritskiy and Korostelev, 2018). E. coli tRNA fMet (Chemical Block) was aminoacylated with [ 35 S]-N-formyl-L-methionine (Perkin Elmer) as described (Lancaster and Noller, 2005).…”
Section: Kinetic Peptidyl Transfer Assaysmentioning
confidence: 99%
“…E. coli tRNA fMet (Chemical Block) was aminoacylated with [ 35 S]-N-formyl-L-methionine (Perkin Elmer) as described (Lancaster and Noller, 2005). 70S ribosomes were prepared from E. coli (MRE600) as described (Svidritskiy and Korostelev, 2018). 70S ribosomes were stored in the ribosome-storage buffer (20 mM Tris-HCl, pH 7.0; 100 mM NH 4 Cl; 20 mM MgCl 2 ) at -80°C.…”
Section: Kinetic Peptidyl Transfer Assaysmentioning
confidence: 99%
See 1 more Smart Citation